Corporate Social Responsibility, Leverage, Kepemilikan Asing, dan Nilai Perusahaan dengan Firm Size sebagai Pemoderasi - Loriyani, Ni Nengah; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi; Vol 33 No 10 (2023)DO - 10.24843/EJA.2023.v33.i10.p07, 2023)
Company value is an important factor that companies must pay attention to because it reflects the prosperity received by shareholders. The aim of this research is to obtain empirical evidence of the influence of CSR, leverage, and foreign ownership on company value with firm size as a moderator, which has relatively little to do with Investor33. This research fills the gap in the 2018-2020 period. The sample was determined using a purposive sampling technique and a sample of 45 observations was obtained. The data analysis technique used is Moderated Regression Analysis. The research results show that CSR has a positive effect on firm value, leverage has a negative effect on firm value, foreign ownership has no effect on firm value, firm size weakens the effect of CSR on firm value, firm size weakens the negative effect of leverage on firm value, and firm size does not moderate the effect foreign ownership on company value. Keywords: Firm Value; Corporate Social Responsibility; Leverage; Foreign Ownership; Firm Size.